ISO 19902 ENVIRONMENTAL LOAD FACTOR FOR 3-LEG AND 4-LEG STEEL JACKET PLATFORMS DESIGNS IN WATERS AROUND MADURA - Rikanti Tawekal, Jessica
The Working Stress Design (WSD) method adopted in the API RP2A WSD standard code has long been used in designing jacket platforms in Indonesia, so this method has proven to be capable. But now, industry experts have started to switch to using the Load and Resistance Factor Design (LRFD) method, which is considered more appropriate because it applies the safety factor to the load and partial structural resistance. This partial safety factor shows that the LRFD approach considers the variability of each load and structural resistance. Thus, the LRFD method provides more consistent reliability than the WSD method, which only uses a single safety factor. Currently, the ISO 19902 standard code is the latest standard code to adopt the LRFD method, while API RP2A WSD is the latest standard code to adopt the WSD method. The environmental load factor listed in ISO 19902 results from calibration for the Gulf of Mexico and the North Sea. Based on data processing carried out in the study, the variability of wave height in the Gulf of Mexico can reach 40%. In comparison, the variability in the waters around Madura only ranges up to 22%. This difference in variability indicates that the environmental load factors listed in ISO 19902 need to be calibrated to Indonesian waters. Suppose the factors listed in ISO 19902 are currently applied in Indonesian waters. In that case, the resulting structural design will be overdesign because the environmental load factor accommodates higher uncertainty in environmental load than it should be. ISO 19902 also states that this geographically dependent environmental load factor needs to be calibrated using a reliability-based method. In environmental load factor calibration, a reliability target value must be achieved according to ISO 19902; reliability that is based on the degree of the consequence of structural failure or reliability from other methods that have been proven feasible or qualified to be used. The reliability of the API RP2A WSD design structure, which has been practiced for a long time in Indonesia, is chosen as the reliability target. This research is correlative with the combination of quantitative and qualitative approaches and uses simulation techniques in data processing. The dissertation research took environmental data in the waters around Madura, which is the current oil and gas working area. The 3-leg flare platform and 4-leg wellhead platform will be used for the calibration study. Environmental parameter data was taken from a secondary database named SEAFINE. SEAFINE provides hourly data for winds and waves for 60 years and hourly data for currents for 20 years. This research began with a statistical analysis of wave height, current speed, and wind speed data. The statistical analysis results showed that the lognormal or normal distribution could adequately describe the randomness of wind, wave, and tidal current based on the results of the K-S test. Using the lognormal and normal distribution will estimate design parameters more conservatively, and reliability analysis can be carried out more easily. Afterwards, the structure will be designed according to the procedures stated in ISO 19902 and API RP2A WSD. From the structural design obtained, it can be concluded that the design of the flare platform is governed by environmental load, and the environmental load governs only the wellhead platform design in the Java Sea. The large topside load on the wellhead platform and the shallower water depth in the Madura Strait make the design of the wellhead platform in the Madura Strait more dominated by the gravity of the structure. Reliability analysis in the failure mode of component stress failure during in-place analysis was chosen because the environmental load factor is a factor that will be applied to the in-place analysis. In addition, the reliability is also conducted for plastic collapse failure, which was carried out to observe the effect of redundant components on the in-place phase design on global structural failure. In reliability analysis, yield stress and modulus of elasticity are assumed to be random variables in structural resistance. Wave height and current velocity are considered as random variables on environmental loads. In contrast, wind speed is assumed to be a deterministic variable because of its minor influence on the design of the jacket structure. The calibration process is carried out until the ISO 19902 environmental load factor value provides a structural design with a reliability value similar to that of a structure designed using API RP2A WSD. The calibration results in the waters around Madura for both platforms indicate that the recommended environmental load factor is 1.23 based on component stress failure and 1.25 based on plastic collapse failure. In the end, it was concluded that the recommended environmental load factor is to be 1.25, so the jacket platform design in the waters around Madura would produce reliability that is equal to or greater than the reliability of the API RP2A WSD design structure.